The PIKfyve Inhibitor YM201636 Blocks the Continuous Recycling of the Tight Junction Proteins Claudin-1 and Claudin-2 in MDCK cells - Dukes, Joseph D.; Whitley, Paul; Chalmers, Andrew D. (PLOS ONE, 2012)
Tight junctions mediate the intercellular diffusion barrier found in epithelial tissues but they are not static complexes; instead there is rapid movement of individual proteins within the junctions. In addition some tight junction proteins are continuously being endocytosed and recycled back to the plasma membrane. Understanding the dynamic behaviour of tight junctions is important as they are altered in a range of pathological conditions including cancer and inflammatory bowel disease. In this study we investigate the effect of treating epithelial cells with a small molecule inhibitor (YM201636) of the lipid kinase PIKfyve, a protein which is involved in endocytic trafficking. We show that MDCK cells treated with YM201636 accumulate the tight junction protein claudin-1 intracellularly. In contrast YM201636 did not alter the localization of other junction proteins including ZO-1, occludin and E-cadherin. A biochemical trafficking assay was used to show that YM201636 inhibited the endocytic recycling of claudin-1, providing an explanation for the intracellular accumulation. Claudin-2 was also found to constantly recycle in confluent MDCK cells and treatment with YM201636 blocked this recycling and caused accumulation of intracellular claudin-2. However, claudin-4 showed negligible endocytosis and no detectable intracellular accumulation occurred following treatment with YM201636, suggesting that not all claudins show the same rate of endocytic trafficking. Finally, we show that, consistent with the defects in claudin trafficking, incubation with YM201636 delayed formation of the epithelial permeability barrier. Therefore, YM201636 treatment blocks the continuous recycling of claudin-1/claudin-2 and delays epithelial barrier formation.